LEARNING OBSTACLE SISWA PADA MATERI OPERASI HITUNG BENTUK ALJABAR MELALUI SOAL PEMECAHAN MASALAH MATEMATIS - Fasya, Robby Ismail; Suryadi, Didi; Nurjanah, Nurjanah (Universitas Insan Budi Utomo, 2024)
This study aims to identify learning obstacles faced by students on the material of arithmetic operations of algebraic forms through mathematical problem solving. Student learning obstacle in this study were obtained through analyzing the test results of algebraic form calculation operation material through mathematical problem solving questions and interviews with students. The research method used is a qualitative method with a case study approach. The participants of this study involved 6 students in one of the high schools in Bekasi City, West Java Province. The results of this study indicate that some students experience learning obstacle in solving problems of arithmetic operations of algebraic forms through mathematical problem solving. The identified learning obstacle include (1) conceptual ontogenic obstacle, (2) instrumental ontogenic obstacle, (3) psychological ontogenic obstacle, (4) epistemological obstacle, and (5) potential didactic obstacle.